Venous and Arterial Thrombosis Associated with HIV Infection - Dentali, Francesco; Nicolini, Eleonora; Ageno, Walter (Seminars in Thrombosis and Hemostasis, 2012)
The advent of highly active antiretroviral therapy (HAART) and the appropriate use of prophylactic strategies to prevent opportunistic infections have drastically decreased human immunodeficiency virus (HIV) infection-related mortality. However, there is growing evidence that metabolic abnormalities associated with HIV infection and with its treatment may lead to an increased risk of cardiovascular (CV) events. Several studies showed an increased risk of symptomatic and subclinical CV events in these patients. On the other hand, the association with venous thromboembolic events is less compelling. This increased risk is possibly explained by the coexistence in this population of different risk factors determined by the HIV infection per se, by the higher prevalence of traditional CV risk factors such as obesity, smoking, hypertension, hyperlipidemia, and glucose intolerance, as compared with the general population, and by the effects of HAART. Thus, systematic identification and aggressive treatment of traditional risk factors seem to be necessary to prevent the development of cardiovascular disease in this population.
Keywords: human immunodeficiency virus; acquired immunodeficiency syndrome; venous thrombosis; arterial thrombosis